Análise dos efeitos da Propriedade Estatal sobre o desempenho financeiro das multinacionais brasileiras e de suas subsidiárias - Alcântara, Juciara Nunes de (2017)
The objective of this research was to verify what are the effects that the state ownership of the Brazilian multinationals have on the financial performance of the subsidiaries located abroad. The study, developed in three chapters, has a general introduction that presents the general characteristics of the government investment pattern in Brazilian multinationals, and describes the investments of these multinationals abroad. The second and third chapter respectively present the results of the analyzes of the effects of state ownership on the performance of multinationals and subsidiaries. The study considers the direct state properties, in which the federal government is the controlling shareholder, and the indirect one, referring to the investment of public banks and pension funds of public institutions. The initial database corresponds to the financial data of 422 subsidiaries of 37 Brazilian multinationals distributed in 53 countries in a total of 2264 observations. The final sample of the third chapter consisted of 207 subsidiaries (approximately 50% of the total population). Different techniques were used for data analysis, such as regressions for panel data, generalized moments methods, Heckman two-stage models, and multilevel regressions, which analyzes the effects of the clustering structures of the objects of analysis. There were three main evidences found. The first is related to the favorable effect of state ownership on the performance of the Brazilian multinational, which is independent of the modality of state participation in the structure, whether direct or indirect. The second refers to the relationship between state ownership and investment in tax havens, showing that there is a propensity of the Brazilian government to invest in companies that have subsidiaries in tax havens. The third is linked to the effect on the subsidiaries' performance, showing that state ownership has a multilevel effect, influencing subsidiaries differently within their hierarchical structure. It is interpreted that such evidence has important theoretical and practical implications for the international business field, when discussing how state ownership can influence the different levels of grouping of subsidiaries.